Substitution time of natural food by artificial diet on survival rate and growth of pacific white shrimp (Litopenaeus vannamei) postlarvae during rearing in low salinity media - Ferdinand Hukama Taqwa; Daniel Djokosetiyanto; Ridwan Affandi (Jurnal Akuakultur Indonesia)
This research was conducted to determine natural food substitution time by artificial diet   after salinity acclimatization from 20 ppt until 2 ppt, which can increase survival and growth of (Litopenaeus vannamei) postlarvae during rearing period. Design experiment was completely randomized design with five treatments and three replications of natural food Chironomus sp.  (60% of crude protein) substitution time by artificial diet (40% of crude protein) at day: 1 (A), 7 (B), 14 (C), 21 (D) and full natural food without artificial diet (E) during 28 days rearing period. White shrimp postlarvae and rearing media in this experiment based from best result of earlier research that is PL25 from acclimatization in media 2 ppt with addition of potassium 25 ppm to freshwater media.  The densities of PL25 white shrimp were 20 PLs/50 liters of 2 ppt media. The result of this experiment showed that the use of artificial diet as soon as after salinity acclimatization (PL25) gave best performance production compared to which only that was given natural food Chironomus sp. during experiment or with treatment by artificial diet substitution at day-7, day-14 or day-21, shown with the highest value of food consumption level, protein retention, energy retention, daily growth rate and food efficiency. Survival rate of PL54 was above 80% and not significant different between treatment. That is supported by chemical-physical value of water quality still in range appropriate to survival rate of white shrimp post larvae during a rearing period. The result of this experiment indicated that requirement nutrient of PL25 in low salinity did not fulfilled if only rely on natural food, so that require artificial diet with nutrition content to support growth and survival rate of white shrimp post larvae more maximal.